Functional Evaluation of Fracture Shaft of Humerus Treated By Antegrade Closed Interlocking Nail - Gupta, Pradip Kumar; Chaudhary, Ajay (Birat Journal of Health Sciences, 2020)
Introduction: Management of fractures shaft of humerus is always a challenging problem to deal with as they are very frequently associated with complex multiple injuries. Interlocking nails have gained popularity now a days for stabilization of humeral shaft fractures due to load sharing nature of implant, preservation of fracture hematoma, minimal exposures and rigid fixation with early mobilization.Objective: The objective of the study was to assess the outcome of the fracture shaft of humerus stabilized with interlocking nail.Methodology: A Prospective clinical study was done on fifty patients of fractures shaft of humerus stabilized using antegrade interlocking nail.Results: The most common causes of fractures shaft of humerus was road traffic accident (66%). The average union time was 12.7± 1.3 weeks. About 8% had delayed union and 10% had non-union which were treated with bone graft. There was no deep infection but two (4%)had superficial infection in open Gustilo grade II fracture. Four cases (8%) had radial nerve injury, mostly neuropraxias, which recovered in three months. There were 12 cases of significant restriction of shoulder movements which was resolved in six weeks after guarded physiotherapy.Conclusion: Closed interlocking nailing is a least invasive surgical option available to manage complex humeral shaft fractures.